Laying the Foundations : A Global Analysis of Regulatory Frameworks for the Safety of Dams and Downstream Communities - Wishart, Marcus J.; Ueda, Satoru; Pisaniello, John D.; Tingey-Holyoak, Joanne L.; Lyon, Kimberly N.; Boj García, Esteban (Washington, DC: World Bank, 2020)
Dam safety is central to public protection and economic security. However, the world has an aging portfolio of large dams, with growing downstream populations and rapid urbanization placing dual pressures on these important infrastructures to provide increased services and to do it more safely. To meet the challenge, countries need legal and institutional frameworks that are fit for purpose and can ensure the safety of dams. Such frameworks enable dams to provide water supplies to meet domestic and industrial demands, support power generation, improve food security, and bolster resilience to floods and droughts, helping to build safer communities. Laying the Foundations: A Global Analysis of Regulatory Frameworks for the Safety of Dams and Downstream Communities is a systematic review of dam regimes from a diverse set of 51 countries with varying economic, political, and cultural circumstances. These case studies inform a continuum of legal, institutional, technical, and financial options for sustainable dam safety assurance. The findings from the comparative analysis will inform decisionmakers about the merits of different options for dam safety and help them systematically develop the most effective approaches for the country context. By identifying the essential elements of good practices guided by portfolio characteristics, this tool can help identify gaps in existing legal, institutional, technical, and financial frameworks to enhance the regulatory regime for ensuring the safety of dams and downstream communities.